Diagnosa Penyakit Kulit (Eksim) pada Anak Menggunakan Metode Dempster Shafer - Novi Yunanda Putri; Achmad Fauzi; Victor Maruli Pakpahan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Eczema is a chronic inflammatory skin disease characterized by mild to severe itching, and is recurrent. Eczema mostly appears when children are aged (5-12 years) but also affects many toddlers and adults. The main symptom of eczema is unbearable itching. Various factors cause eczema, including genetic factors related to skin color disorders, immunological disorders, and environmental factors and must be treated immediately or followed up by seeing a specialist.